Augmented reality for understanding electronic components in vocational education - Indra Jati Desrizal; Ika Parma Dewi; Hendra Hidayat; Eko Indrawan (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
Understanding the structure and operation of electronic components is challenging when instruction relies on two-dimensional media because their internal processes are not directly visible. This study developed and evaluated a marker-based Augmented Reality (AR) learning medium for Electronic Components in a vocational Industrial Electronics Engineering programme. Using a Research and Development approach based on the ADDIE model, the AR medium was developed with Unity and Vuforia to provide interactive 3D visualizations of electronic components, including rotation, scaling, and animations of their operation. The medium was validated by three electronics specialists and three media design specialists using Aiken's V, while its practicality was assessed by one teacher and 15 tenth-grade students. Conceptual understanding was measured using a 20-item pretest-posttest administered to the same 15 students. Material and media validity scores were 0.888 and 0.955, respectively, indicating very high validity. Practicality ratings were also very high, reaching 93% from the teacher and 92% from the students. Mean conceptual understanding scores increased from 41 on the pretest to 80.33 on the posttest, with an N-Gain of 0.67, categorized as moderate. Although the one-group design does not establish causality, the findings indicate that AR-based visualization can support students' understanding of abstract electronic concepts and provide a practical instructional model for vocational education.